"I Stopped Shooting Up When I got Married": Desistance, Crime, and Love. Issue 10 (3rd October 2018) - Rayburn, Rachel L.; Wright, James D.
ABSTRACT: This project studies desistance from substance use and homelessness. In the early 1990s, the New Orleans Homeless Substance Abusers Project (NOHSAP) tested new treatment approaches for homeless substance users. The program ran for three years and enrolled 670 clients. The current project involved finding as many of these individuals as possible and reinterviewing them 25 years later. The methodology for this study consists of follow-up interviews with 50 individuals in a variety of settings, including at their homes and in correctional facilities. The principal finding is that stable, successful romantic relationships incline formerly homeless substance abusers to be sober, stably housed, or both. For persons of this description, successful romantic relationships are an important motivator for desistance.